2017
DOI: 10.1016/j.redox.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial GSH replenishment as a potential therapeutic approach for Niemann Pick type C disease

Abstract: Niemann Pick type C (NPC) disease is a progressive lysosomal storage disorder caused by mutations in genes encoding NPC1/NPC2 proteins, characterized by neurological defects, hepatosplenomegaly and premature death. While the primary biochemical feature of NPC disease is the intracellular accumulation of cholesterol and gangliosides, predominantly in endolysosomes, mitochondrial cholesterol accumulation has also been reported. As accumulation of cholesterol in mitochondria is known to impair the transport of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 55 publications
7
72
0
1
Order By: Relevance
“…Buildup of cholesterol seems to directly impair also mitochondrial GSH import, leading to mitochondrial GSH depletion (Torres et al . ). In addition, the authors show that GSH ethyl ester (GSH‐EE), but not N‐acetylcysteine, rescues the mitochondrial GSH pool in both liver and brain of Npc1 −/− mice and in fibroblasts from NPC patients.…”
Section: Mitochondria and Lysosomal Storage Disordersmentioning
confidence: 97%
“…Buildup of cholesterol seems to directly impair also mitochondrial GSH import, leading to mitochondrial GSH depletion (Torres et al . ). In addition, the authors show that GSH ethyl ester (GSH‐EE), but not N‐acetylcysteine, rescues the mitochondrial GSH pool in both liver and brain of Npc1 −/− mice and in fibroblasts from NPC patients.…”
Section: Mitochondria and Lysosomal Storage Disordersmentioning
confidence: 97%
“…A recent study showed that increasing mitochondrial GSH levels by intraperitoneal administration of GSH ethyl ester protected brain cells of NPC1‐deficient mice from oxidative stress, mitochondrial impairment and cell death, and increased maximal life span and survival of these animals (Torres et al . ). These findings underscore the potential of mitochondrially targeted therapies for the treatment of NPCD patients.…”
Section: Mitochondrial Dysfunction In Lysosomal Storage Diseases (Lsd)mentioning
confidence: 97%
“…19 In addition to this, NPC1 mutation induced an increased cholesterol level in mitochondria, leading to alterations in the function of this organelle and in energy metabolism. [20][21][22] Abnormal mitochondrial morphology, depolarization of mitochondrial membrane potential (mMP), respiratory chain deficit, and impaired adenosine triphosphate (ATP) production have been shown in NPC1-depleted Chinese hamster ovary cells as well as in the brain of a mouse model of NPC1 13,21,23 (Balb/c NPC1 À/À model, hereafter indicated as NPC1 mice). Moreover, in an NPC1 cell model, it was demonstrated that an excessive activation and impaired progression of the autophagy could be responsible for the abnormal mitochondrial clearance and of the (most probably subsequent) accumulation of depolarized and fragmented mitochondria.…”
Section: Pathogenetic Mechanisms Involved In Npc1 Diseasementioning
confidence: 99%